ENCLOSED IS A COPY OF THE GSA'S SMOKING REGULATIONS WHICH APPEARED IN YESTERDAY'S FEDERAL REGISTER (Tufts Archival Research Center, 2007)
Letter to Horace Kornegay of the Tobacco Institute containing the regulations put forth by GSA on smoking. Advises that while it is perfectly logical to ban smoking elevators, hazardous areas and closed shuttle vehicles, other places such as government audotoriums, classrooms and conference rooms do not need any regulations.